2010
DOI: 10.1037/a0019407
|View full text |Cite
|
Sign up to set email alerts
|

Positive parenting, family cohesion, and child social competence among immigrant Latino families.

Abstract: The relation between positive parenting, family cohesion, and child social competence was examined among Latino families (predominantly from Mexico) who were recent immigrants to the United States. A mixed method study was conducted, including both pre- and post-test self-reported surveys (9-month interval) and qualitative data from focus groups. A total of 282 parents and 282 children (ages 9-12) participated in the survey study. Results at post-test follow-up indicated that family cohesion predicted improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(119 citation statements)
references
References 37 publications
6
103
0
10
Order By: Relevance
“…Firstly, migration to a new country and culture often challenges familial roles and responsibilities and may also cause changes in family organisation and functioning [35][36][37]. Leidy et al [12] for instance note that one of the challenges to positive parenting is a lack of extended family members who previously helped with raising children. Changes in family organisation and functioning may in turn lead to stress which, during pregnancy, can expose the foetus to elevated levels of stress hormones and possibly influence the development of stress systems [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, migration to a new country and culture often challenges familial roles and responsibilities and may also cause changes in family organisation and functioning [35][36][37]. Leidy et al [12] for instance note that one of the challenges to positive parenting is a lack of extended family members who previously helped with raising children. Changes in family organisation and functioning may in turn lead to stress which, during pregnancy, can expose the foetus to elevated levels of stress hormones and possibly influence the development of stress systems [38].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have focused on how family factors contribute to the presence of problem behaviour in ethnic minority children [11][12][13]. Weiss et al [11] demonstrated that the family's reliability on internal coping strategies was a risk factor for problem behaviour in Latino children residing in the US.…”
Section: Introductionmentioning
confidence: 99%
“…There is ongoing debate about the role of adolescents in immigrant families and the impact that role has on adolescent development (Leidy, Guerra & Toro, 2010;Trickett & Jones, 2007). Adolescent children of immigrants often find themselves in positions where they take on nontraditional roles in the family that can result in a shift in the power between the parent and the child.…”
Section: Adolescent and Youth-centered Servicesmentioning
confidence: 99%
“…Positive parenting and family cohesion ultimately lead to positive adolescent development (Ali, Liu, & Humedian, 2004;Leidy, Guerra, & Toro, 2010). Having services that target the needs of parents is integral in building a healthy family system (Trickett & Jones, 2007).…”
Section: Parent and Family-centered Servicesmentioning
confidence: 99%
“…Cumsille & Epstein, 1994;Wentzel & Feldman, 1996). Family cohesion leads to improvements in adolescent social problem-solving skills and social self-efficacy (Leidy, Guerra, & Toro, 2010), while low levels of family cohesion result in an earlier onset of romantic and sexual experience (De Graaf, van de Schoot, Woertman, Hawk, & Meeus, 2012). Family cohesion is also related to young adults' well-being (Crespo et al;Fosco et al, 2012) and lower levels of stress and depression (Fosco et al, 2012;Johnson, Gans, Kerr, & Deegan, 2008;Reinherz, Paradis, Giaconia, Stashwick, & Fitzmaurice, 2003) during early adulthood.…”
mentioning
confidence: 99%